DEVELOPMENT OF ECONOMIC THINKING IN THE YOUNGER GENERATION - Babaeva Sabinabonu Davronbek qizi (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract:  The  article  analyzes  the  economic  thinking  of  young  people,  its significance  and  ways  of  formation  in  the  modern  world.  It  examines  key  factors influencing  the  development  of  economic  knowledge  among  youth,  including education,  family  traditions,  accessibility  of  information  technologies,  and globalization.  Special  attention  is  paid  to  financial  literacy  for  successful  social adaptation,  as  well  as  challenges  young  people  face  such  as  lack  of  experience, consumer culture, and psychological barriers. The article suggests solutions through educational programs, mentorship, and promotion of financial self-education.